Efeitos da adubação com manipueira sobre o rendimento e qualidade dos frutos de tomate - Vieites, Rogério Lopes [UNESP] (My University, 1998)
The objective of this research was to evaluate the residue from cassava, known as manipueira, as an alternative for tomato (Lycopersicon esculentum) fertilization. This experiment was carried out in UNESP with the cultivar Rio Grande. The experimental design was a completely randomized blocks in a 3 × 3 factorial arrangement with five blocks. Treatments constituted the following: 1) witness; 2) 54 m3/ha of manipueira; 3) 108 m3/ha of manipueira; 4) half recommended mineral fertilization; 5) half recommended mineral fertilization + 54 m3/ha of manipueira; 6) half recommended mineral fertilization + 108 m3/ha of manipueira; 7) recommended mineral fertilization; 8) recommended mineral fertilization + 54 m3/ha of manipueira and 9) recommended mineral fertilization + 108 m3/ha of manipueira. Tomato yield, number of fruits per plant, fruit diameter and lenght, total soluble solids (TSS), total titratable acidity (TTA) and the ratio TSS/TTA were evaluated. The results obtained indicated that manipueira contributed significantly to yield and quality of pos-harvested tomato fruits.

Este trabalho teve por objetivo avaliar a manipueira como uma alternativa de adubo para o tomateiro (Lycopersicon esculentum). O ensaio foi conduzido no Campus Experimental da UNESP com a cultivar Rio Grande. O delineamento experimental foi o de blocos ao acaso com esquema fatorial 3 x 3, com cinco repetições. O experimento constou dos seguintes tratamentos: 1) testemunha; 2) 54 m3/ha de manipueira; 3) 108 m3/ha de manipueira; 4) metade da adubação mineral recomendada; 5) metade da adubação mineral recomendada + 54 m3/ha de manipueira; 6) metade da adubação mineral recomendada + 108 m3/ha de manipueira; 7) adubação mineral recomendada; 8) adubação mineral recomendada + 54 m3/ha de manipueira; e 9) adubação mineral recomendada + 108 m3/ha de manipueira. Foram avaliados o rendimento, número de frutos por planta, diâmetro e comprimento dos frutos, teores de sólidos solúveis totais (SST), acidez total titulável (ATT) e a relação SST/ATT. De acordo com os resultados obtidos pode-se concluir que a manipueira contribuiu para o aumento do rendimento e qualidade pós-colheita dos frutos na fase pós-colheita.
Effects of fertilization with cassava residues on yield and fruit quality of tomato
Keywords: Cassava residues; Fertilization; Lycopersicon esculentum